2020
DOI: 10.1097/eja.0000000000001297
|View full text |Cite
|
Sign up to set email alerts
|

Long-term psychological and physical outcomes of women after postdural puncture headache

Abstract: BACKGROUND Postdural puncture headache after accidental dural puncture during labour may lead to chronic sequalae. OBJECTIVES We aimed to measure the incidence of postpartum depression, posttraumatic stress disorder, chronic headache, backache and breastfeeding rates after a postdural puncture headache. DESIGN A retrospective, case-matched cohort study. SETTING A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 44 publications
2
23
0
1
Order By: Relevance
“…and chronic backache 17.9%-23.9% in women with accidental dural puncture without or with an epidural blood patch. This confirms previous reports 8,9,18 which found chronic headache rates from 17.6% to 34.8% and chronic backache rates of 28 to 43.9%. Our study is the first study that excluded any women who had a history of chronic headaches or history of backaches.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…and chronic backache 17.9%-23.9% in women with accidental dural puncture without or with an epidural blood patch. This confirms previous reports 8,9,18 which found chronic headache rates from 17.6% to 34.8% and chronic backache rates of 28 to 43.9%. Our study is the first study that excluded any women who had a history of chronic headaches or history of backaches.…”
Section: Discussionsupporting
confidence: 93%
“…While EBP is considered the gold standard for the treatment of PDPH, 6,19 there is not much information on its long‐term effects. Like the study by Webb et al 9 and Orbach‐Zinger et al, 18 we found no difference in rates of chronic headache and backache in women who received an EBP as opposed to those who did not. It is unclear, however, how the severity of the PDPH headache impacted the development of headache.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Post Dural Puncture Headache is the most common complication of neuraxial anesthesia which has been postulated that it is resulting from intracranial hypotension due to continuous loss of CSF through the dural tear that is mainly related to needle size, shape, type, and less likely risk factor including female gender, young age, pregnancy, low BMI, previous history of PDPH, and history of migraine headache (4,12,20,24,38,42,43). In turn, these causes prolonged bedridden and thrombosis, decrease early breastfeeding and mother-to-child bonding, length of hospital stay, increased psychological distress, and dissatisfaction to the mother and her family (13,16,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Accidental dural puncture (ADP) is a serious complication of obstetric anesthesia 1 2. Although several studies have identified specific risk factors, there remains a need for modifiable etiologies3 4 There has been growing interest in root cause analysis, an exploration of key system-level factors as contributors to the occurrence of accidents 3.…”
Section: Introductionmentioning
confidence: 99%